Simulation study of the influence of the ionospheric layer height in the thin layer ionospheric model - Brunini, Claudio Antonio (2011)
This work aims to contribute to the understanding of the influence of the ionospheric layer height (ILH) on the thin layer ionospheric model (TLIM) used to retrieve ionospheric information from the GNSS observations. Particular attention is paid to the errors caused on the estimation of the vertical total electron content (vTEC) and the GNSS satellites and receivers inter-frequency biases (IFB), by the use of an inappropriate ILH. The work relies upon numerical simulations performed with an empirical model of the Earth’s ionosphere: the model is used to create realistic but controlled ionospheric scenarios and the errors are evaluated after recovering those scenarios with the TLIM. The error assessment is performed in the Central and the northern part of the South American continents, a region where large errors are expected due to the combined actions of the Appleton Anomaly of the ionosphere and the South-Atlantic anomaly of the geomagnetic field. According to this study, there does not exist a unique ILH that cancels the vTEC error for the whole region under consideration. The ILH that cancels the regional mean vTEC error varies with the solar activity and season. The latitude-dependent conversion error propagates to the parameters of the model used to represent the latitudinal variation on the vTEC on the ionospheric layer, and to the IFB, when these values are simultaneously estimated from the observed sTEC. Besides, the ILH that cancels the regional mean vTEC error is different from the one that cancels the IFB error and the difference between both ILH varies with the solar activity and season.